X Chromatin inactivation in Menopause: A study on Hindu caste Bengalee population - Mukherjee, Koel; Chatterjee, Diptendu; Bandyopadhyay, Arup Ratan (Asian Journal of Medical Sciences, 2018)
Background: Menopause being a physiologic event and eventually the prime time to perform risk assessment of chronic diseases and initiate preventive health measures. Previous studies reported, later menopause is independently associated to increased risk of breast and endometrial cancer. The menopausal status is determined and influenced by intrinsic factors. Majority of the studies on menopause from Indian context, especially on Bengalee Hindu Caste population confined to socio demographic issues, attitudes, problems and quality of life. However, relatively little work is attempted to unravel the complex interplay of genetics and epigenetic mechanisms, the effect on menopause. In this background it seems to be an urgent need to understand menopause status objectively, to approach the interplay of genetics and epigenetic mechanisms of menopausal status by X chromatin inactivation. Aims and Objective: Best of the knowledge it is the first attempt to evaluate the prevalence of X chromatin inactivation in menopausal women among Bengalee Hindu Caste population. Materials and Methods: Sex chromatin inactivation was evaluated from 100 each pre and post menopausal women from the buccal smear of each individuals. After fixation and staining of altogether 20000 (twenty thousand) cells were scanned from the Bengalee Hindu Caste for a comparison of menopausal women and their menarcheal counterparts. Results: Result demonstrated significantly decreased (P<0.001) prevalence of X chromatin inactivation sites among the menopausal females in comparison to their menarcheal women counterpart. Conclusion: The present study vindicated possible association between the presence of sex hormone receptors and the prevalence of sex chromatin and also envisaged the role of X chromatin inactivation for early prognosis of menopause. Asian Journal of Medical Sciences Vol.9(3) 2018 41-45